Discovery of Viral Myosin Genes With Complex Evolutionary History Within Plankton - Kijima, Soichiro; Delmont, Tom O.; Miyazaki, Urara; Gaia, Morgan; Endo, Hisashi; Ogata, Hiroyuki (Frontiers in Microbiology, 2021)
Nucleocytoplasmic large DNA viruses (NCLDVs) infect diverse eukaryotes and form a group of viruses with capsids encapsulating large genomes. Recent studies are increasingly revealing a spectacular array of functions encoded in their genomes, including genes for energy metabolisms, nutrient uptake, as well as cytoskeleton. Here, we report the discovery of genes homologous to myosins, the major eukaryotic motor proteins previously unrecognized in the virosphere, in environmental genomes of NCLDVs from the surface of the oceans. Phylogenetic analyses indicate that most viral myosins (named “virmyosins”) belong to the Imitervirales order, except for one belonging to the Phycodnaviridae family. On the one hand, the phylogenetic positions of virmyosin-encoding Imitervirales are scattered within the Imitervirales. On the other hand, Imitervirales virmyosin genes form a monophyletic group in the phylogeny of diverse myosin sequences. Furthermore, phylogenetic trends for the virmyosin genes and viruses containing them were incongruent. Based on these results, we argue that multiple transfers of myosin homologs have occurred not only from eukaryotes to viruses but also between viruses, supposedly during co-infections of the same host. Like other viruses that use host motor proteins for their intracellular transport or motility, these viruses may use the virally encoded myosins for the intracellular trafficking of giant viral particles.